The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.eclinm.2019.03.014
|View full text |Cite
|
Sign up to set email alerts
|

An Individual Participant Data Meta-analysis of Maternal Going-to-Sleep Position, Interactions with Fetal Vulnerability, and the Risk of Late Stillbirth

Abstract: Background Maternal supine going-to-sleep position has been associated with increased risk of late stillbirth (≥ 28 weeks), but it is unknown if the risk differs between right and left side, and if some pregnancies are more vulnerable. Methods Systematic searches were undertaken for an individual-level participant data (IPD) meta-analysis of case–control studies, prospective cohort studies and randomised trials undertaken up until 26 Jan, 2018, that reported data on mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(107 citation statements)
references
References 35 publications
4
98
1
1
Order By: Relevance
“…In keeping with the findings of others we found that women in Australia who were born in South Asia, Africa and Oceania are at higher risk of having a stillbirth after 24 weeks gestation compared to locally born women, even after adjustment for confounders.…”
Section: Discussionsupporting
confidence: 92%
“…In keeping with the findings of others we found that women in Australia who were born in South Asia, Africa and Oceania are at higher risk of having a stillbirth after 24 weeks gestation compared to locally born women, even after adjustment for confounders.…”
Section: Discussionsupporting
confidence: 92%
“…Participants comprised 851 late stillbirth cases and 2257 controls with ongoing pregnancies from five eligible case-control studies (Fig 1): the Auckland Stillbirth Study [26], the New Zealand Multicentre Stillbirth Study [31], the Sydney Stillbirth Study [27], the UK Midlands and North of England Stillbirth Study [30], and the International Study of Trends and Associated Risks for Stillbirth Study [32], comprising women of many ethnicities [24]. Differences in maternal and pregnancy characteristics, infant size, and going-to-sleep position between cases and controls have been previously reported (S1 Table) [24]. 'Any' snoring (cases n = 473, 56.0%; controls, n = 1182, 54.1%), sleep quality (fairly bad to very bad, cases n = 248, 33.5%; controls, n = 703, 35.3%), daytime sleepiness (positive ESS score �10, cases n = 128, 17.5%; controls n = 312, 15.8%), and frequency of getting up to use the toilet (�1 per night, cases n = 667, 90.0%; controls, n = 1820, 91.5%) last month were not associated with late stillbirth in the univariable analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The study population comprised cases with late stillbirth and controls with ongoing pregnancies from the CRIBSS data. This IPD meta-analysis was registered with the PROSPERO register of systematic reviews (CRD42017047703) and followed the IPD meta-analysis protocol [38], search strategy [24], risk of bias for non-randomised studies (ROBINS-E) tool [39], and published results [24]. Five international case-control studies [26,27,[30][31][32] that collected maternal going-to-sleep position and late stillbirth data were included in this pooled IPD meta-analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations